Dampak Penggunaan Handphone terhadap Aktivitas Belajar Siswa Siswi Sekolah Menengah Pertama di Kota Medan - Ayu Andini; Dian Novitri; Dini Lestari (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
The rapid advancement of data and communication technology affects every aspect of human life. The world of education is no exception. For communication purposes, cell phones or cell phones can have a positive and negative influence on student learning activities. The purpose of this study was to identify the impact of mobile phone use on the learning activities of junior high school students in Medan City. This research uses quantitative methods. Where the information collection method used in this study is a questionnaire. This study provides information that the use of mobile phones affects the learning activities of students in high school. But cell phones also have bad consequences. These include disturbing eye health, making students forget when to study, and viewing inappropriate photos for students to see. Reality reports that 100% of students are dependent on cell phones.